(untitled) (Universal International Scientific Journal, 2026)
The article examines the formation and evolution of the concept of entrepreneurship in the economic literature (risk/adverse conditions, differentiation from the owner of capital, innovation and the “discovery” function) and uses this theoretical framework to explain how entrepreneurial activity accelerates and transforms in the digital economy. The impact of the digital economy on entrepreneurship is analyzed on the example of Uzbekistan, including directions and practical problems (infrastructure, digital skills, private sector participation) within the framework of the “Digital Uzbekistan-2030” strategy.